2014
DOI: 10.11604/pamj.2014.17.179.3788
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of enterobacteriaceae isolated from HIV-infected patients in Kinshasa

Abstract: IntroductionPeople infected by Human Immunodeficiency Virus (HIV) are susceptible to develop severe bacterial infections. We set out to determine the frequency and the sensitivity to antibiotics of enterobaceriaceae isolated from urine and feces of HIV-infected persons.MethodsUrine and feces samples were collected from HIV-infected patients of the Centre de Traitement Ambulatoire de Kabinda (CTA/Kabinda, Kinshasa) and analyzed at the Reference National Laboratory for HIV/AIDS and Sexually Transmitted Infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Furthermore, the low resistance (0.8%) of the isolates in this study to ertapenem, as well as 15.8%, 18.3% and 18.7% resistance of the isolates to ciprofloxacin, gentamicin and ceftazidime, respectively is in agreement with a previous report onenteric pathogens isolated from stool samples of HIV-infected individuals attending Anti-retroviral Clinic in Hawassa University Hospital, Ethiopia, where a low resistance patterns were observed to nalidixic acid, gentamicin, norfloxacin, ceftriaxone and ciprofloxacin [29]. Similarly, a low resistance patterns similar to the observation from this study was also reported among the Enterobacteriaceae isolated from HIV-infected patients in Kinshasa to gentamicin [30]. In addition, the 38.3%, 14.5% and 15.8% resistance of the isolates in the present study to trimethoprim/Sulfamethoxazole, amoxicillin/clavulanate and ciprofloxacin, respectively contradicts the previously reported 25.0%, 66.0% and 66.7% resistance to the respective antibiotics from a study carried out on similar isolates from HIV and AIDS patients in Bugando Medical Centre, Mwanza, Tanzania [31].The reason for the noticed differences may be as a result of the study samples.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the low resistance (0.8%) of the isolates in this study to ertapenem, as well as 15.8%, 18.3% and 18.7% resistance of the isolates to ciprofloxacin, gentamicin and ceftazidime, respectively is in agreement with a previous report onenteric pathogens isolated from stool samples of HIV-infected individuals attending Anti-retroviral Clinic in Hawassa University Hospital, Ethiopia, where a low resistance patterns were observed to nalidixic acid, gentamicin, norfloxacin, ceftriaxone and ciprofloxacin [29]. Similarly, a low resistance patterns similar to the observation from this study was also reported among the Enterobacteriaceae isolated from HIV-infected patients in Kinshasa to gentamicin [30]. In addition, the 38.3%, 14.5% and 15.8% resistance of the isolates in the present study to trimethoprim/Sulfamethoxazole, amoxicillin/clavulanate and ciprofloxacin, respectively contradicts the previously reported 25.0%, 66.0% and 66.7% resistance to the respective antibiotics from a study carried out on similar isolates from HIV and AIDS patients in Bugando Medical Centre, Mwanza, Tanzania [31].The reason for the noticed differences may be as a result of the study samples.…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe an association between immunological or virological markers (VL and CD4 count) and gut microbiome diversity measures. In contrast, other studies showed significantly lower microbiome diversity in those with more severe HIV status [ 9 , 37 , 38 ]. Findings of previous studies may have been affected by sample size and ART duration.…”
Section: Discussionmentioning
confidence: 71%
“…We found enriched levels of Enterobacteriaceae in HIV-infected participants with low CD4 + T-cell counts (≤400 cells/mm 3 ). Enterobacteriaceae may cause GI and urinary tract infections in HIV-infected children [ 38 ]; however, the clinical significance is unclear, because Enterobacteriaceae are found as part of the normal intestinal flora. Burkholderiaceae, also enriched in those with low CD4 + T-cell counts (≤400 cells/mm 3 ), includes species known to cause severe lung infections in patients with cystic fibrosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, Highly Active Antiretroviral Therapy(HAART), a group of different classes of drugs that are used in the treatment of HIV [6], and prophylactic management of opportunistic infections have significantly improved clinical outcomes and overall survival of HIV-infected individuals; others have reported reduced diarrhoeal episodes in bacterial GE [7]. On the other hand, the treatment of diarrhoea in HIV-infected individuals remains a major challenge in this era of marked antimicrobial resistance [8,9]. This problem is ascribed to frequent visits to health facilities for medical check-ups and continuous exposure to antibiotic therapy and prophylaxis [9,10].…”
Section: Introductionmentioning
confidence: 99%